Ring-Shaped Magnetic Anomaly in the Wiborg Batholith, Loviisa: Geophysical Surveys and Bedrock Mapping - Penttinen, Karoliina (My University, 2025)
This master’s thesis investigates a ring-shaped magnetic anomaly in the Loviisa area, identified through aeromagnetic data from the Geological Survey of Finland (GTK). The study area lies in the southwestern side of Wiborg rapakivi batholith. The research aims to determine the cause of this anomaly using field magnetometry, bedrock mapping, petrophysics, and geochemistry. Field magnetometry shows that the strongest anomalies correspond to wiborgite, a magnetically intense rapakivi type rich in iron-bearing minerals like magnetite and iron-rich biotite. In contrast, even-grained rapakivi granite exhibits weaker anomalies due to its lower magnetic mineral content. Bedrock mapping confirms wiborgite’s extensive presence, aligning with petrophysical and geochemical findings. These analyses suggest that wiborgite formed from earlier magma pulses with higher magnetic mineral concentrations, whereas later magma pulses, such as even-grained and rare-ovoidic rapakivi granites, contain fewer magnetic components. The results support existing models linking ring-shaped magnetic structures to sequential magmatic intrusions in rapakivi batholiths. Understanding such anomalies can improve interpretations of similar formations elsewhere.

Tässä pro gradu -tutkielmassa tutkitaan Loviisan alueella havaittua rengasmaista magneettista anomaliaa, joka on tunnistettu Suomen geologian tutkimuskeskuksen (GTK) ilmakartoitusaineistossa. Tutkimusalue sijaitsee Wiborgin rapakivibatoliitin lounaisosassa. Työn tavoitteena on selvittää anomalian syy yhdistämällä maastomagnetometriaa, kallioperäkartoitusta, petrofysiikkaa ja geokemiaa. Maastomagnetometriset mittaukset osoittavat, että voimakkaimmat anomaliat liittyvät wiborgiittiin, magneettisesti voimakkaampaan rapakivityyppiin, joka sisältää enemmän rautapitoisia mineraaleja, kuten magnetiittia ja rautarikkaampaa biotiittia. Sen sijaan tasarakeinen rapakivigraniitti tuottaa heikompia anomalioita alhaisemman magneettisten mineraalien pitoisuutensa vuoksi. Kallioperäkartoituksessa havaittu wiborgiitin laaja esiintyminen tukee petrofysikaalisia ja geokemiallisia tuloksia, joiden mukaan se edustaa varhaisempia, enemmän magneettisia mineraaleja sisältäviä magmapulsseja. Myöhäisemmät magmapulssit, kuten tasarakeinen ja harvaovoidinen rapakivigraniitti, sisältävät vähemmän magneettisia komponentteja. Tulokset tukevat aiempia malleja, joissa rengasmaiset magneettiset rakenteet liittyvät rapakivibatoliittien vaiheittaiseen magmaattiseen intrudoitumiseen. Näiden anomalioiden tarkempi ymmärtäminen voi edistää samankaltaisten rakenteiden tulkintaa muilla rapakivialueilla.
Keywords: rapakivi, geophysics, anomaly, magnetic survey, petrophysics, geochemistry, Loviisa, Finland, geofysiikka, anomalia, Suomi